2003
DOI: 10.1002/adsc.200303141
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Heck Cross‐Coupling Catalysis: A Pseudo‐Pharmaceutical Approach

Abstract: The problem of predicting the activity of ligands and solvents in homogeneous catalysis is addressed. A systematic selection method for ligands and solvents is presented, using a combination of stereoelectronic and electrotopological descriptors to describe the ligands and solvents in a set of 500 Heck reactions. Libraries of −virtual ligands× and −virtual solvents× are projected on the reaction space, and their reactivity is then predicted using multivariate models. The applications of this approach to combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 40 publications
0
33
0
Order By: Relevance
“…The PCA and PLS treatment of this dataset is described in detail in our previous paper. [9] Regression Analysis Two different regression methods were used in this study: artificial neural networks (ANN) and multiple linear regression analyses. [7] ANNs attempt to mimic the fault-tolerance and capacity to learn of biological neural systems by modeling the low-level structure of the brain.…”
Section: Experimental Section -Computational Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PCA and PLS treatment of this dataset is described in detail in our previous paper. [9] Regression Analysis Two different regression methods were used in this study: artificial neural networks (ANN) and multiple linear regression analyses. [7] ANNs attempt to mimic the fault-tolerance and capacity to learn of biological neural systems by modeling the low-level structure of the brain.…”
Section: Experimental Section -Computational Methodsmentioning
confidence: 99%
“…[6 -8] Recently, we examined the application of the QSAR approach to a set of literature data of Heck cross-coupling reactions. [9] Although the reaction mechanism is reasonably well understood, the complexity of the data and the predominance of non-linear effects precluded a full analysis with classical linear methods. Nevertheless, we demonstrated that useful knowledge can be extracted regarding the activity of ligands and solvents.…”
Section: Introductionmentioning
confidence: 99%
“…The advantage is that the relationship between spaces B and C can be quantified using QSAR and quantitative structureproperty relationship (QSPR) models. [10,11] Note that space B contains molecular descriptor values, rather than structures, but these are related directly to the structures, as we showed recently for the cases of monodentate complexes in Pd-catalysed Heck reactions, [12,13] and bidentate complexes in Ni-catalysed hydrocyanation. [14] Therefore, if one can generate a sufficiently large number of sufficiently diverse structures in space A, and link the spaces A and B, one should be able to predict the relevant figures of merit in space C using QSAR/ QSPR descriptor models.…”
Section: Theory Defining the Catalyst Spacementioning
confidence: 83%
“…[11] Here we introduce an additional parameter, the variable importance (VIP), to estimate the contribution of each descriptor in the PLS model. PLS modelling is a simultaneous projection of the variables matrix X and the figures of merit matrix Y on lower-dimensional hyper-planes.…”
Section: Methodsmentioning
confidence: 99%
“…[11] This model was used to preselect candidates from large virtual libraries of monodentate ligands. [13] In this paper, we extend the work to reactions catalysed by bidentate ligands, presenting descriptor models for nickel-catalysed hydrocyanation.…”
Section: Introductionmentioning
confidence: 99%